2000
DOI: 10.1016/s0008-6363(00)00102-4
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effect of resveratrol, a natural antioxidant derived from grapes

Abstract: Resveratrol is a potent antiarrhythmic agent with cardioprotective properties in I-R rats. The cardioprotective effects of resveratrol in the I-R rats may be correlated with its antioxidant activity and upregulation of NO production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
268
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 505 publications
(278 citation statements)
references
References 38 publications
2
268
0
8
Order By: Relevance
“…Furthermore, RS suppresses inflammation by inhibiting cyclooxygenase-1, -2; lipoxygenases, epoxygenases and synthesis of prostaglandins and eicosanoids (Saiko et al, 2008). Hattori et al (2002) and Hung et al (2000) demonstrated the inhibition of inflammation and atheromatous plaque formation by RS through altering the nitric oxide generation from vascular endothelium. RS modulates the production and secretion of inflammatory mediators and thereby suppresses the thrombogenic function of polymorphonuclear cells (Rotondo et al, 1998).…”
Section: Anti-inflammatory Effects Of Rsmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, RS suppresses inflammation by inhibiting cyclooxygenase-1, -2; lipoxygenases, epoxygenases and synthesis of prostaglandins and eicosanoids (Saiko et al, 2008). Hattori et al (2002) and Hung et al (2000) demonstrated the inhibition of inflammation and atheromatous plaque formation by RS through altering the nitric oxide generation from vascular endothelium. RS modulates the production and secretion of inflammatory mediators and thereby suppresses the thrombogenic function of polymorphonuclear cells (Rotondo et al, 1998).…”
Section: Anti-inflammatory Effects Of Rsmentioning
confidence: 94%
“…RS has been demonstrated to exert a variety of health benefits including anti-atherogenic, anti-inflammatory and anti-cancer effects (Das and Maulik, 2006;Sun et al, 2008;Udenigwe et al, 2008). RS has also been shown to offer protection against ischemic injuries (Wang et al, 2002a) and neurodegenerative diseases (Fremont, 2000;Hung et al, 2000;Sun et al, 2002). A number of studies exist regarding the beneficial effects of RS on cardiovascular disease (CVD) with the positive effects being attributed to its anti-oxidant (Fauconneau et al, 1997;Martinez and Moreno, 2000;Sato et al, 2000) and anti-coagulative properties (Bertelli et al, 1996b;Soleas et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Prowadzi to do zahamowania syntezy tromboksanu A2 w leukocytach szczurów (substancji biologicznie czynnej zaliczanej do eikozanoidów, która powoduje m.in. agregację płytek krwi [16]. Ponadto wykazano, że dodatek resweratrolu do hodowli ludzkich komórek raka wątroby HepG2 zahamował syntezę apolipoproteiny B, cholesterolu i triacylogliceroli [28,33].…”
Section: Resweratrol a Ryzyko Przewlekłych Chorób Niezakaźnychunclassified
“…Narażenie kardiomiocytów na stres, a następnie poddanie ich działaniu resweratrolu, powoduje zmniejszenie stresu oksydacyjnego, wzrost aktywności enzymów zapobiegających powstawaniu wolnych rodników i nasilenie syntezy tlenku azotu (NO). Ma to ogromne znaczenie przy niedokrwieniu narządów i powoduje ich ochronę przed powikłaniami: arytmią, krótkotrwałą mechaniczną dysfunkcją i śmiercią komórek [6,15,37].Inną przyczyną kardioprotekcyjnego działania resweratrolu jest wpływ na proces agregacji płytek krwi i metabolizm trombiny [16,37]. Udowodniono, że już niewielka ilość czerwonego wina może zmniejszać zawartość wskaźników stanu zapalnego, agregację płytek krwi i tworzenie zakrzepów.…”
unclassified
“…In recent years, interest in RSV has substantially increased and its broad biological activity at the cellular level has been demonstrated. The biological properties are listed below: cardioprotective (Hung et al, 2000), anti-neoplastic (Atten et al, 2005), antiinflammatory and anti-oxidant (de la Lastra & Villegas, 2007). Preclinical studies have suggested that RSV simulates the effects of calorie restriction (Barger et al, 2008).…”
Section: Introductionmentioning
confidence: 99%